The Moderator Role of Individual Goal Clarity in the Relationships between Career Goal Discrepancies and Distresses - Dian R. Sawitri, PhD.; Mirwan Surya Perdhana; Bambang Suryadi (Journal of Educational, Health and Community Psychology, 2019)
Abstract Discrepancies between individuals and their parents regarding career goals often present as inevitable conditions that have the potentials to influence individual career distress and also parental career distress from the perspective of the individual. This study aimed to investigate the moderating role of individual goal clarity on the relationships between individual-parent career goal discrepancies and individual and parental career distresses. We collected data from 205 freshmen of an university in Semarang, Indonesia, M age = 18.35 years, SD age = .64, 68.3% female. We used the Individual-Parent Career Goal Discrepancies Scale (α = .93), Goal Clarity Scale (α = .84), Career Distress Scale (α = .87), and Parental Career Distress Scale(α = .81). Hierarchical regression analyses demonstrated that as discrepancies increased, individual and parental career distress increased for high goal clarity and low goal clarity groups. However, those variables increased more markedly for the low goal clarity group. Our results highlight the important role of individual goal clarity in the consequences of individual-parent career goal discrepancies on young people’s and parental distresses. Recommendations for students, parents, and practitioners are discussed. Keywords: career, discrepancies, distress, goal clarity, parents